Advances in monitoring and modelling algal blooms in freshwater reservoirs : general principles and a case study of Macau - Lou, Inchio; Han, Boping; Zhang, Weiying (Springer, 2016)
This book describes essential principles of and approaches to monitoring and modeling algal blooms. Freshwater algal blooms have become a growing concern worldwide. They are caused by a high level of cyanobacteria, particularly Microcystis spp. and Cylindrospermopsis raciborskii, which can produce microcystin and cylindrospermopsin, respectively. Since long-term exposure to these cyanotoxins may affect public health, the reliable detection and quantification of these harmful algae species has become a priority in water quality management. The book utilizes an advanced monitoring approach to identify and quantify cyanobacteria species and various cyanotoxin-producing genotypes. Further, it uses a modeling approach to forecast the occurrence of the phytoplankton that causes algal blooms in freshwater reservoirs, providing a comprehensive picture of currently available micro- and macro-techniques for studying the problem of algal blooms. As such, it offers a valuable guide for researchers, graduate students and professional engineers engaged in monitoring and modeling water quality in lakes and reservoirs.
Keywords: Algal blooms -- Monitoring -- China -- Macau.; China -- Macau.; elektronické knihy; electronic books